Komputerisasi Sistem Pelayanan di Koperasi Jasa Keuangan Syariah Wanita Melati Harapan - ., Budiono; Wulandari, Yustina Retno (JURNAL GAUNG INFORMATIKA, 2009)
Barokah is store that sales goods such as appliances household. It records all transaction in simple note. This allows the difference in the amount of inventory. Therefore the system needs to be made computer-based inventory information as an alternative to solve problem on the old system. Inventory system is built and developed using data modeling with DFD, implemented using the Delphi programming language and using Paradox database as data storage. The information generated from this inventory system which reports the data item, supplier data, purchase order, and sales transactions. Based on the results of questionnaire that was distributed to 30 respondents obtained that more than 50% of respondents said the system can be fast in service, ease of performance, easy to use, and easy to understand.